Cost-effectiveness of oral cancer screening: results from a cluster randomized controlled trial in India - Sujha Subramanian, Rengaswamy Sankaranarayanan, Bela Bapat, Thara Somanathan, Gigi Thomas, Babu Mathew,Jissa Vinoda & Kunnambath Ramadas (Bull World Health Organ 2009;87:200-206 | doi:10.2471/BLT.08.053231, 2009)
Objective To evaluate oral cancer screening by visual inspection. Methods A cluster randomized controlled trial was initiated in Trivandrum district, Kerala, India. Of 13 population clusters, seven were randomly allocated to three rounds of screening between 1996 and 2004, while standard care was provided in six (control arm). An activity-based approach was employed to calculate costs associated with various components of the screening trial. Information on the resources used and on clinical events in each trial arm was derived from trial databases. Total costs for each cluster were estimated in 2004 United States dollars (US$). The incremental cost per life-year saved was calculated for all eligible individuals and for high-risk individuals (i.e. tobacco or alcohol users). Findings The proportion of oral cancers detected at an early stage (i.e. stage I or II) was higher in the intervention arm than the control arm (42 per cent versus 24 per cent, respectively). The incremental cost per life-year saved was US$ 835 for all individuals eligible for screening and US$ 156 for high-risk individuals. Oral cancer screening by visual inspection was performed for under US$ 6 per person. Conclusion The most cost-effective approach to oral cancer screening by visual inspection is to offer it to the high-risk population. Targeted screening of this group will ensure that screening can be offered at a reasonable cost in a limited-resource setting